Optimization of phase change process in a sinusoidal-wavy conductive walled cylinder with encapsulated-phase change material during magnetohydrodynamic nanofluid convection - Selimefendigil, Fatih; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Elsevier, 2022)
A novel method of controlling the phase transition dynamics in encapsulated phase change material (PCM) installed container is proposed by using combined utilization of magnetic field and wavy conductive wall during hybrid nanoliquid convection. The study is performed for different values of Reynolds number (Re: 100-500), strength of magnetic field (Ha: 0-30), amplitude (Af: 0-0.2), wave number (Nf: 2-16) of the wavy partition and conductivity ratio (Kr: 0.1-50). Binary nanoparticle loading with solid volume fraction of 2% is considered. The complete phase transition time (PT) is reduced by about 46.7% and 22.5% for flat and wavy conductive walls between the lowest and highest Re cases. The impact of using magnetic field is favorable for phase transition while as compared to flat wall by using wavy wall, PT is reduced by further about 9% with the magnetic field at the highest strength. Corrugation amplitude and wave number are good control parameters for affecting the phase transition dynamics while PT variation is 30% when cases with lowest and highest wave number of corrugation are compared. Phase change is faster with higher conductivity ratio while up to 42.3% reduction in PT is obtained by varying conductivity ratio. Optimization assisted computational fluid dynamics is used to achieve the fastest phase transition dynamics while optimum set of parameters are obtained as (Ha, Af, Kr)=(30, 0.067, 2.7) at Re=100 and (Ha, Af, Kr)=(30, 0.007, 1.30) at Re=500.
Keywords: Wavy conductive wall; Phase transition dynamics; Hybrid nanofluid; CFD; Optimization